J.M. Coetzee and the novel writing and politics afer Beckett - Hayes, Patrick, 1976- (Oxford : Oxford University Press, 2010)
This book argues that the significance of Coetzee's complex & finely-nuanced fiction lies in the acuity with which it both explores & developes the tradition of the novel - ranging from Cervantes, Defoe, & Richardson, to Dostoevsky, Kafka, & Becket - as part of a sustained attempt to rethink the relationship between writing & politics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Coetzee, J. M., -- 1940- -- Criticism and interpretation; Politics and literature